Conservation of a permanent hypersaline lake: management options evaluated from decadal variability of Coleofasciculus chthonoplastes microbial mats. Issue 4 (6th December 2012) - De Wit, Rutger; Guerrero, Maria‐Carmen; Legaz, Alfredo; Jonkers, Henk M.; Blocier, Laëtitia; Gumiaux, Charles; Gautret, Pascale
ABSTRACT 'La Salada de Chiprana' (NE Spain) is a permanent athalassic saline lake, and as such unique in Western Europe. More than 20 years ago, it was recognized that this lake should be protected; particularly, because it supported extensive microbial mat communities built by the cyanobacterium Coleofasciculus (Microcoleus) chthonoplastes and submerged aquatic vegetation of an endemic form of the foxtail stonewort (Lamprothamnium papulosum var. papulosum f. aragonense). For centuries, the lake hydrology, salinity and water levels have been driven by the combined effects of anthropogenic activities (e.g. irrigation in the watershed) and climatic factors. In the early 1990s, the water level increased and salinity dropped as a consequence of excessive freshwater inputs from direct overflow via irrigation canals. As a result, the microbial mats and aquatic vegetation perished and water column turbidity increased. Based on these observations, since 1994 management measures were introduced aimed at reducing the freshwater input by stopping the direct overflow from irrigation canals. This resulted in a rapid recovery of the hypersaline features of the lake, particularly of the microbial mat communities and the aquatic vegetation. Since 2000, there has been a persistent trend of decreasing lake level and increasing salinity. The population of the endemic foxtail stonewort collapsed in 2006 and the area occupied by C. chthonoplastes mats has drastically decreased. This raises the important question on how to manage athalassic saline lakes in their agrocultural context and calls for a review of the management option taken in the early 1990s. While it could be argued that the current situation is closer to natural hydrological functioning than 20 years ago, we propose that management should seek to conserve the original microbial and aquatic vegetation communities. Copyright © 2012 John Wiley & Sons, Ltd.